Museo di Torino igazgatóságához - Irmédi-Molnár László (Fond 165 Irmédi-Molnár László, 1965)
Fond 165 Irmédi-Molnár László > Irmédi-Molnár László iratai. > Irmédi-Molnár László levelezése. > Irmédi-Molnár László levélfogalmazványai